2005
DOI: 10.1007/s00586-004-0830-1
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal lumbar interbody fusion: a safe technique with satisfactory three to five year results

Abstract: The unilateral transforaminal approach for lumbar interbody fusion as an alternative to the anterior (ALIF) and traditional posterior lumbar interbody fusion (PLIF) combined with pedicle screw instrumentation is gaining in popularity. At present, a prospective study using a standardized tool for outcome measurement after the transforaminal lumber interbody fusion (TLIF) with a follow-up of at least 3 years is not available in the current literature, although there have been reports on specific complications an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
130
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(142 citation statements)
references
References 41 publications
9
130
1
2
Order By: Relevance
“…Our fusion rate of single-level surgeries compares favorably to those previously reported in the literature for patients undergoing conventional lumbar arthrodesis [7,9,13,15]. On the other hand, the multilevel fusion group revealed a low fusion rate.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our fusion rate of single-level surgeries compares favorably to those previously reported in the literature for patients undergoing conventional lumbar arthrodesis [7,9,13,15]. On the other hand, the multilevel fusion group revealed a low fusion rate.…”
Section: Discussionsupporting
confidence: 80%
“…Schwender et al [25] reported an average 32% improvement in the Oswestry Disability Index score postoperatively, with an average followup of 22.6 months. When comparing with traditional open transforaminal lumbar interbody fusion, average improvements in the Oswestry Disability Index score of 43% at 2 years and 24% at the latest followup between 35 and 64 months postoperatively were noted in patients with isthmic spondylolisthesis [9]. The Spine Patient Outcomes Research Trial found a 24% improvement in the Oswestry Disability Index score at 2 years postoperatively in patients with degenerative spondylolisthesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…The pseudarthrosis rate was higher in both of our study groups than usually reported for APF and TLIF techniques [16,24,28,32]. In fact, fusion assessment was based on a very strict and detailed scale resulting in a very critical look at fusion results.…”
Section: Discussionmentioning
confidence: 59%
“…Because of its posterolateral extracanalar discectomy and fusion, it has been reported as a safe technique, without the potential complications described when using combined APF and PLIF techniques [17,28]. Several authors have published retrospective studies comparing the TLIF technique to APF [16,18,35]. However, these studies included multiple diagnostic groups, and clinical as well as radiological outcomes were not always reported.…”
Section: Introductionmentioning
confidence: 99%
“…In large curves, structural anterior column support provides several benefits, including improved stability, decreased stress on screws, higher fusion rates, and better lumbar lordosis [16,17,26,30,31,39]. Nevertheless, instrumented arthrodesis procedures are not free of complications, and considering all the comorbidities associated with an older population, surgical treatment of degenerative scoliosis should be carefully studied to avoid them.…”
Section: Introductionmentioning
confidence: 99%